Ground Beef Inspections and E. Coli O157:H7: Placing the Needs of the American Beef Industry Above Concerns for the Public Safety - Katherine A. Straw (Washington University Journal of Law & Policy, 2011)
Millions of Americans suffer from foodborne illnesses each year. While mild cases often get shrugged off after spending a night in the bathroom, a small number of people suffer drastic consequences for liking their burgers medium rare. Consumers take for granted, and are reassured by, the presence of a “USDA inspected” sticker on their meat products. Part I of this Note reviews the history of federal regulation of the beef industry, discusses the particular dangers of Escherichia coli 0157:57 (“E. coli O157:H7”) as a foodborne pathogen, outlines the inspection systems implemented in response to outbreaks of E. coli O157:H7 outbreaks, and explains current recall practices for potentially contaminated products. Part II analyzes the shortcomings of the current regulatory framework for ground beef inspections and the ability of the beef industry to “pass the buck” when contaminated beef products make their way out to the public. Part III proposes legislation that would grant the government the ability to mandate recalls of contaminated products and to fine those companies who do not properly inspect their products or maintain sanitary processing facilities.
Keywords: Beef industry; Cattle; Food safety; Foodborne diseases; Foodborne illness; Meat inspection; United States; E. Coli